Awareness and Knowledge of Liver Diseases in Relation to Demographic Variables in the General Population of Pakistan - Ashraf, Saira; Malik, Ayesha; Din, Rafi Ud (Biological and Clinical Sciences Research Journal, 2025)
Liver diseases are a growing public health concern worldwide, yet public awareness and understanding of these conditions remain inadequate. Objectives: To assess the level of awareness and knowledge regarding liver diseases among patients and examine how these vary according to demographic factors such as age, gender, education, and residence. Methods: This cross-sectional, observational study was conducted at the Gastroenterology Outpatient and Indoor departments at Combined Military Hospital Lahore from 1st February 2025 till 30th April 2025. All patients meeting the inclusion criteria will be asked to fill out a standard questionnaire, the regional liver index study, and some questions from previously done research assessing the patients' knowledge, attitude, and practice regarding chronic liver disease. Data were collected using a structured questionnaire. Results: Out of 200 participants, 75% reported general awareness of liver diseases, with hepatitis being the most recognized condition (60%). However, only 19% of respondents demonstrated good knowledge, while 43% and 38% had moderate and poor knowledge. Knowledge levels were significantly associated with education level (p < 0.001) and place of residence (p = 0.03), but not with gender (p = 0.22). Only 28% were aware of the hepatitis B vaccine. Traditional media and the internet were the most cited sources of information. Conclusion: It is concluded that although awareness of liver diseases exists among the population, specific knowledge remains limited, particularly among individuals with lower educational levels and those in rural areas. Targeted educational initiatives are needed to bridge this knowledge gap and improve liver health outcomes.